ANALISA PENGARUH DISTORSI HARMONISA SAAT PENGOPERASIAN FILTER HYBRID TERHADAP UNJUK KERJA MOTOR INDUKSI 3 FASA - Ary Susiawan, Kadek; Rinas, I Wayan; Suartika, I Made (Jurnal SPEKTRUM; Vol 8 No 3 (2021): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2021.v08.i03.p9, 2021)
The increasing. use of non-linear loads can make. harmonic distortion in the current and voltage waves so that it can reduce the. reliability and quality of the. power system. Non-linear loads that are often used are induction motors, consequently the use of induction. motors will have an impact on the high harmonics. of the system. The impact. of these harmonics can be reduced by using a. hybrid filter. The method used is. direct measurement of the object under study in the form. of current data, motor rotation and 3 induction motor THDi. This research uses a Simulink-based simulation. which aims to reduce the. harmonic content in. the network and to see the effect of harmonics. on the performance of the. 3-phase induction motor on rotation and torque. The. results of the. analysis show. that the hybrid filter. can. reduce the harmonic content in the network. The decrease that occurs in THDi is 11.96% in the R phase, 11.95% in the S. phase and 11.96% in the T phase with a load of 3 motors. Using hybrid power filter is able to make the motor rotation stable at 0.17 s. However, the rotation. of the. induction motor remains at. 1498 rpm and a torque of 0.4682 Nm.